A framework for improved classroom communication in the South African schooling context. Issue 3 (March 2021) - Fredericks, Brenton; Alexander, Gregory
Abstract: The way in which information is conveyed should contribute positively to learners' overall learning experience and development. Knowledge transfer is a communication activity in the classroom and should therefore be effective. In the study reported in this article, an exploratory mixed method approach was applied to collect data regarding educators' perceptions of communication in South African schools. The results reveal the ways in which effective communication improves learner achievement, and conversely, how ineffective communication leads to a communication breakdown, misunderstanding and poor learner achievement. An educator communication framework is proposed to improve classroom communication in South African schools. Abstract : Communication, knowledge transfer, schooling context.